Nanomaterial ZnO-TiO2 (at) MSC as well as preparation method and application thereof
By preparing nanocomposite ZnO-TiO2@MSC, modified corn straw powder and doped TiO2@MSC and ZnO nanoparticles, the problem of insufficient antibacterial effect of TiO2 nanoparticles under visible light was solved, and effective prevention and treatment of tomato leaf spot disease and promoting plant growth was achieved.
Patent Information
- Application Number
- CN202510710068.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-29
- Publication Date
- 2025-08-26
AI Technical Summary
TiO2 nanoparticles have insufficient antibacterial effects under visible light, which limits their effectiveness in pesticide applications. Traditional chemical pesticides have problems of environmental pollution and enhanced resistance to pathogenic bacteria.
The nanocomposite ZnO-TiO2@MSC was prepared, and the nanocomposites were modified corn stalk powder was used as a support, and TiO2@MSC and ZnO nanoparticles were doped, and the hydroxyl radicals were released using visible light to kill Pseudomonas syringae and prevent and treat tomato leaf spot disease.
Nano-composite ZnO-TiO2@MSC effectively kills pathogenic bacteria under visible light, promotes tomato growth, improves photosynthetic rate, transpiration rate and water utilization efficiency, prevents and treats tomato leaf spot disease, and reduces environmental pollution.
Smart Images

Figure CN120530979A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of pesticides, and more specifically, relates to a nano-composite material ZnO-TiO2@MSC and a preparation method and application thereof. Background Art
[0002] Bacterial plant diseases are caused by bacteria that infect plants through natural openings and wounds and are spread by water or insects. These diseases primarily include soft rot, canker, bacterial wilt, and leaf spot. While traditional control methods include selecting resistant varieties and using pesticides and antibiotics, these methods are often labor-intensive and can pose environmental risks.
[0003] Traditional chemical pesticides pose problems such as environmental pollution and increased resistance in pathogens. Nanomaterials, due to their unique physicochemical properties, have been widely used in the pesticide field. For example, nanomaterials can serve as pesticide carriers, improving their stability and dispersibility, and can also be used as antibacterial materials for the prevention and treatment of bacterial plant diseases. However, while single metal oxides, such as TiO2 nanoparticles, can produce antibacterial effects using ultraviolet light as an excitation source, they are limited by the wavelength of the excitation light. Only when TiO2 is excited by light with an energy greater than the band gap can the holes or electron pairs generated react with oxygen and water in the environment. The resulting reactive oxygen species and other free radicals react chemically with organic molecules in cells, decomposing the cells and achieving an antibacterial effect. This limits the effectiveness of TiO2 nanoparticles in pesticide applications. Visible light, on the other hand, is a common light source with a wide wavelength range and is relatively readily available. Therefore, the technical problem addressed by the present invention is how to modify TiO2 nanoparticles so that they produce an antibacterial effect even under visible light. Summary of the Invention
[0004] The purpose of the present invention is to provide a nanocomposite material ZnO-TiO2@MSC and a preparation method and application thereof.
[0005] To achieve the above object, the technical solution adopted by the present invention is: The preparation method of the nanocomposite material ZnO-TiO2@MSC comprises the following steps: S1. Soaking corn straw in a hydrochloric acid solution to remove heavy metals, washing it, treating it with an ammonium hydroxide solution to expose its pore structure, and then drying and crushing it to obtain modified straw powder; S2, adding an acid solution catalyst to the titanium source premix to initiate sol formation; adding the modified straw powder to the sol, stirring to produce a gel, drying the gel and then gradient calcining to obtain TiO2@MSC, thereby preparing a TiO2@MSC suspension; S3, mixing the TiO2@MSC suspension and the ZnO nanoparticle suspension to obtain a mixed suspension, stirring the mixed suspension to generate a precipitate doped with TiO2@MSC and ZnO nanoparticles, removing the solvent, washing, drying, and calcining the precipitate at a constant temperature to obtain a nanocomposite material ZnO-TiO2@MSC; The volume ratio of anhydrous ethanol, tetrabutyl titanate and acetylacetone in the titanium source premix is 20:10:1; The volume ratio of the acid solution catalyst, which is 60% to 70% by mass of nitric acid solution, water and anhydrous ethanol, is 1.1:9:32; The mass volume ratio of the modified straw powder, titanium source premix, and acid solution catalyst is 0.5 g:93 mL:42.1 mL; The mass ratio of TiO2@MSC and ZnO nanoparticles in the mixed suspension is 1:1.
[0006] The nanocomposite material ZnO-TiO2@MSC in the present invention uses modified straw powder as a carrier. After adding a titanium source premix to generate a gel, the gel is calcined to obtain TiO2@MSC. TiO2@MSC and ZnO are then doped and calcined to obtain the nanocomposite material ZnO-TiO2@MSC. This nanocomposite material can effectively kill Pseudomonas syringae ( Pseudomonas syringae ), promote tomato growth, increase tomato net photosynthetic rate, transpiration rate, stomatal conductance and water use efficiency, thereby playing a role in preventing and controlling tomato leaf spot disease.
[0007] Furthermore, in S1, the gradient calcination procedure is as follows: starting from the air ambient temperature, heating to 500°C at a heating rate of 10°C / min for 90 min, then heating to 550°C for 90 min, and finally heating to 600°C for 90 min; In S2, the constant temperature calcination condition is 500°C for 180 min.
[0008] The present invention also provides a nanocomposite material ZnO-TiO2@MSC prepared by the above method.
[0009] The present invention also provides use of the nanocomposite material ZnO-TiO2@MSC in preparing an antibacterial product, wherein the antibacterial product is a pesticide or an antibacterial agent.
[0010] Furthermore, the pesticide is a pesticide for preventing and treating tomato leaf spot.
[0011] Furthermore, the pathogen of tomato leaf spot disease is Pseudomonas syringae.
[0012] Furthermore, the concentration of the nanocomposite material ZnO-TiO2@MSC in the pesticide is 2000 μg / mL.
[0013] The present invention also provides application of the nanocomposite material ZnO-TiO2@MSC in preparing a tomato growth promoting product.
[0014] Furthermore, the tomato growth promotion includes promoting the growth of tomato plant height, leaf length and root length, and improving the net photosynthetic rate, transpiration rate, stomatal conductance and water use efficiency of tomatoes.
[0015] The present invention has the following beneficial effects: This invention utilizes corn straw, an agricultural byproduct, as the base material for nanoparticle preparation to create a ZnO-TiO2@MSC nanocomposite. This nanocomposite promotes the oxidation process in target pathogenic bacteria and the consumption of antioxidant biomolecules, resulting in a strong antibacterial effect. It also enhances the plant's own defenses to prevent and control bacterial leaf spot disease in tomatoes. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Figure 2 shows the free radical capture diagram of the nanocomposite ZnO-TiO2@MSC.
[0017] Figure 2 Effect of nanocomposite ZnO-TiO2@MSC on Pseudomonas syringae Pst .DC3000 toxicity assessment chart, the scale coordinates in the chart are bacterial survival rate, the unit is %.
[0018] Figure 3 This is a graph showing the change in malondialdehyde content under the action of the nanocomposite material ZnO-TiO2@MSC. The scale coordinates in the figure are the malondialdehyde content, and the unit is mmol / mL.
[0019] Figure 4 Effect of nanocomposite ZnO-TiO2@MSC on Pseudomonas syringae Pst .DC3000 protein content effect diagram.
[0020] Figure 5 Effect of nanocomposite ZnO-TiO2@MSC on Pseudomonas syringae Pst DC3000 conductivity and damage degree influence diagram. A is the relative conductivity diagram, and B is the damage degree diagram.
[0021] Figure 6Figure 1 shows the effects of different concentrations of ZnO-TiO2@MSC nanocomposites on tomato leaves and plants infected with leaf spot disease. Figure A shows the effects of different concentrations of ZnO-TiO2@MSC nanocomposites on tomato leaves infected with leaf spot disease, and Figure B shows the effects of different concentrations of ZnO-TiO2@MSC nanocomposites on tomato plants infected with leaf spot disease.
[0022] Figure 7 This is a diagram showing the effect of different concentrations of nanocomposite ZnO-TiO2@MSC on leaf disease incidence.
[0023] Figure 8 The graph shows the control effect of ZnO-TiO2@MSC nanocomposite materials with different concentrations on tomato pathogens and the total bacterial count on leaves.
[0024] Figure 9 This figure shows the effects of different concentrations of nanocomposite material ZnO-TiO2@MSC on the growth and development of tomato plants.
[0025] Figure 10 This figure shows the effect of different concentrations of nanocomposite ZnO-TiO2@MSC on the root length of tomato plants.
[0026] Figure 11 The following diagram shows the effects of different concentrations of the nanocomposite ZnO-TiO2@MSC on the photosynthetic parameters of tomato plants. A is the photosynthetic rate, B is the transpiration rate, C is the stomatal conductance, and D is the water use efficiency. DETAILED DESCRIPTION
[0027] The present invention is described in detail below with reference to specific examples, but these examples should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the following examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources.
[0028] Example 1: Preparation method of nanocomposite material ZnO-TiO2@MSC.
[0029] 1. Preparation of Modified Straw Powder: The corn stalks are manually hulled to expose the core, and then thoroughly washed with distilled water to remove impurities. The washed corn stalks are dried in a forced air oven at 60°C for 24 hours. The dried corn stalks are cut into 5 mm thick cylindrical slices. The slices are treated with a 3% hydrochloric acid solution for 48 hours to remove heavy metals, including lead and cadmium. The slices treated with hydrochloric acid are repeatedly washed with distilled water until the pH reaches neutral. The washed slices are immersed in a 5% ammonium hydroxide solution for 12 hours to remove pore-blocking substances such as lignin and hemicellulose, expose the pore structure, and enhance adsorption capacity. The ammonium hydroxide-treated material is then washed, dried, ground, and sieved through a 100-mesh sieve to obtain the final modified straw powder.
[0030] 2. Synthesis of TiO2@MSC: 60 mL of anhydrous ethanol was added to a beaker and heated to 65°C with magnetic stirring. 30 mL of tetrabutyl titanate was added dropwise to the ethanol over 30 minutes. Then, 3.0 mL of acetylacetone was added and stirred for 30 minutes to form a titanium source premix. An acid solution catalyst was prepared by mixing 1.1 mL of 65% nitric acid, 9.0 mL of deionized water, and 32.0 mL of anhydrous ethanol. This acid solution catalyst was added dropwise to the titanium source premix to initiate sol formation. 0.5 g of pretreated straw powder was added to the sol and stirred for 4 hours until the solvent evaporated, producing a gel. The gel was dried in an 80°C oven for 12 hours. The dried material was then calcined in a muffle furnace and ground to yield TiO2@MSC. The gradient calcination conditions are: starting from air ambient temperature, heating at 10°C / min to 500°C for 90 min, then heating to 550°C for 90 min, and finally heating to 600°C for 90 min.
[0031] 3. Preparation of ZnO nanoparticles: 1.024 g of zinc acetate was weighed and added to 120 mL of ethylene glycol. The mixture was magnetically stirred in a water bath at 70°C for 60 min. Then, 20 mL of 0.3 mol / L NaOH solution was added dropwise. The mixture was stirred in a water bath at 70°C for 4 hours to form a white gel precipitate. The mixture was then hydrothermally reacted at 160°C for 24 hours to form a precipitate. After the reaction was completed, the precipitate was removed and washed multiple times with anhydrous ethanol and deionized water, dried at 60°C, and ground to obtain ZnO nanoparticles.
[0032] 4. Synthesis of the ZnO-TiO2@MSC nanocomposite: Disperse 0.5 g of TiO2@MSC in 50 mL of ultrapure water and stir for 30 minutes to obtain a TiO2@MSC suspension. Simultaneously, stir 0.5 g of zinc oxide nanoparticles in 100 mL of ultrapure water for 120 minutes to obtain a ZnO nanoparticle suspension. Add the TiO2@MSC suspension dropwise to the ZnO nanoparticle suspension and continue stirring for 180 minutes. The resulting mixture is centrifuged at 10,000 rpm for 10 minutes and washed sequentially with distilled water and ethanol. Dry at 60°C for 12 hours and calcine the dried powder in a muffle furnace at 500°C for 180 minutes to obtain the ZnO-TiO2@MSC nanocomposite, referred to as ZnO-TiO2@MSC.
[0033] Example 2: Antibacterial mechanism of ZnO-TiO2@MSC.
[0034] 1. Determination of main active substances.
[0035] In order to study which active substances in ZnO-TiO2@MSC play a major role, a free radical capture experiment was conducted. The relevant capture agents were added to the photocatalytic antibacterial reaction system to inactivate the corresponding active substances, and indirectly determine which active substances in ZnO-TiO2@MSC are dominant in the sterilization process. 0.05mmol / L potassium dichromate, 0.5mmol / L isopropyl alcohol, 0.5mmol / L p-benzoquinone, and 0.05mmol / L sodium oxalate were used as capture agents, and the corresponding free radicals were captured in the order of their release. - ,•OH,•O2 - 、h + Four free radicals. The operation method is: take 20mL, 10 9 CFU / mL of Pseudomonas syringae Pst DC3000 bacterial solution was mixed evenly with 20 mL of 2000 μg / mL ZnO-TiO2@MSC and 5 mL of the corresponding capture agent was added. The mixture was irradiated with a 300 W xenon lamp for 150 min, and samples were taken every 30 min. The mixture was then diluted to 10 μg / mL with PBS buffer. -5 CFU / mL, 10 -6 CFU / mL, 10 -7 Three CFU / mL gradients were used, and 100 μL of each gradient was evenly spread on solid King's B medium and cultured for 48 h. The results were judged by the change in the total number of colonies.
[0036] The experimental results are as follows Figure 1As shown, free radical scavenging experiments identified the key active species in the bactericidal mechanism. The effect of potassium dichromate addition was negligible, indicating that free electrons contribute minimally to the photocatalytic process. The relative importance of active species is •OH > •O2 - >h + , indicating that hydroxyl radicals are the main antimicrobial agents.
[0037] 2. Effect of ZnO-TiO2@MSC on bacterial activity.
[0038] In order to study the effects of TiO2, TiO2@MSC and ZnO-TiO2@MSC prepared in Example 1 on Pseudomonas syringae Pst The effect of DC3000 on bacterial activity was detected by thiazolyl blue colorimetry. Pst .DC3000 bacterial solution diluted to 10 6 CFU / mL, and then reacted with the nanosuspensions of three samples of TiO2, TiO2@MSC and ZnO-TiO2@MSC at a concentration of 2000μg / mL for a certain period of time, and samples were taken every 30 minutes for later use. Then 1000μL of the test bacterial solution was mixed evenly with 200μL of thiazolyl blue solution and incubated at 30℃ for 4h, followed by centrifugation at 1200rpm / min for 7min, the supernatant was discarded, and an equal amount of dimethyl sulfoxide was added, and the solution was shaken in a shaker to completely dissolve the crystallized product. Finally, 100μL of the solution was placed in a 96-well plate to measure the OD 570 King's B medium was used as the control group. The bacterial survival rate was calculated using the following formula.
[0039] Bacterial survival rate = [(OD A -OD B ) / (OD B -OD C )]×100.
[0040] Where OD A is the absorbance value of the sample group well, OD B is the absorbance value of the control group well, OD C is the absorbance value of the blank well.
[0041] The experimental results are as follows Figure 2 As shown in the figure, after 150 minutes of treatment, the bacterial survival rates when exposed to TiO2 and TiO2@MSC were 20.23% and 14.57%, respectively. In contrast, the bacterial survival rate when exposed to ZnO-TiO2@MSC dropped to 8.02%, which showed higher bactericidal performance compared with TiO2 and TiO2@MSC.
[0042] 3. Effect of ZnO-TiO2@MSC on bacterial damage.
[0043] Malondialdehyde (MDA) is a key indicator of the body's antioxidant potential. It not only reflects the rate and intensity of lipid peroxidation but also indirectly reflects the level of peroxidative damage within tissues. The MDA content produced by the TiO2, TiO2@MSC, and ZnO-TiO2@MSC materials after exposure to bacteria was determined by condensing MDA, an oxidation product of thiobarbituric acid, with lipid peroxides to form a red product.
[0044] The experimental results are as follows Figure 3 As shown in the figure, at 150 min, the accumulated amounts of malondialdehyde in 2000 μg / mL TiO2, TiO2@MSC and ZnO-TiO2@MSC materials reached 1.04 mmol / mL, 1.81 mmol / mL and 2.63 mmol / mL respectively. The above results show that ZnO-TiO2@MSC has the strongest effect on lipid peroxidation, and its photocatalytic process is the most obvious in Pseudomonas syringae. Pst .A large amount of ROS is generated on the surface of DC3000, causing oxidative damage.
[0045] 4. Effect of ZnO-TiO2@MSC on bacterial membrane protein concentration.
[0046] The change in the concentration of protein leakage from the bacteria can reflect the degree of cell membrane integrity. The test method is the Coomassie Brilliant Blue method. The specific operation method is as follows: (1) Weigh 0.1g of bovine serum albumin, dissolve and dilute to 100mL to obtain a 1mg / mL protein standard solution, and then dilute to prepare protein solutions with protein contents of 0μg / mL, 20μg / mL, 40μg / mL, 60μg / mL, 80μg / mL, and 100μg / mL. (2) Weigh 10mg of Coomassie Brilliant Blue and dissolve it in 5mL of ethanol, then add 10mL of orthophosphoric acid, and finally dilute to 100mL to obtain a Coomassie Brilliant Blue solution with a concentration of 0.1mg / mL. (3) Take 0.5mL of solutions with different protein contents and 5mL of Coomassie Brilliant Blue solution with a concentration of 0.1mg / mL and add them to 6 colorimetric tubes respectively. After mixing and standing for 5min, measure the absorbance at 595nm and draw a standard curve. (4) Take the bacterial solution of 2000 μg / mL TiO2, TiO2@MSC and ZnO-TiO2@MSC after light treatment for 150 minutes, centrifuge at 1200 rpm / min for 7 minutes, and take the supernatant. Repeat the above operation to determine the degree of protein leakage. The blank group uses water instead of bacterial solution.
[0047] The experimental results are as follows Figure 4As shown, ZnO-TiO2@MSC treatment exhibited the most severe protein leakage among the three materials. After 150 minutes of visible light irradiation, the extracellular protein concentration of the bacterial solution reached a high of 92.65 μg / mL. In the blank control group, which did not contain any nanomaterials, the protein released due to self-dissolution and death was only 9.53 μg / mL. These results indicate that light exposure can stimulate the release of more superoxide in ZnO-TiO2@MSC, which can severely damage cell membrane structure and enhance antibacterial efficacy.
[0048] 5. Influence of relative conductivity and damage degree.
[0049] The effect of ZnO-TiO2@MSC on Pseudomonas syringae can be expressed by measuring the changes in relative conductivity and damage in the bacterial solution. Pst .The effect of DC3000 membrane permeability. First, Pseudomonas syringae Pst DC3000 cells were cultured in a shaker at 30°C until logarithmic phase and diluted proportionally to obtain a bacterial suspension. This suspension was then mixed with a 2000 μg / mL ZnO-TiO2@MSC suspension and illuminated for 150 minutes. Samples were taken periodically and the cells were disrupted using an ultrasonic disruptor at 4°C for 10 minutes, with a bursting time of 8 seconds and a rest time of 8 seconds. The relative conductivity of the suspension before and after disruption was measured using a conductivity meter. The blank group consisted of cells without illumination and in the presence of ZnO-TiO2@MSCs; the negative group consisted of cells in the presence of illumination and in the absence of ZnO-TiO2@MSCs; and the experimental group consisted of cells in the presence of illumination and in the presence of ZnO-TiO2@MSCs. The bacterial damage score was calculated using the following formula:
[0050] Bacterial damage degree = [(L3-L0) / (1-L0)]×100.
[0051] Where: L3 is the relative conductivity, L0 is the relative conductivity of the blank group.
[0052] The experimental results are as follows Figure 5 As shown, Pseudomonas syringae treated with ZnO-TiO2@MSC Pst The relative conductivity of DC3000 bacteria showed a significant upward trend, rising from 0.91ms / cm to 1.42ms / cm, and the bacterial damage reached 85% after 150 minutes of light exposure. This indicates that ZnO-TiO2@MSC can act on the cell membrane, disrupting the internal ion homeostasis of the bacteria, affecting the normal barrier of the cytoplasmic membrane, disrupting the normal metabolism of the bacteria, and ultimately leading to the death of Pseudomonas syringae. Pst .Death of DC3000.
[0053] Example 3: Application of ZnO-TiO2@MSC in the prevention and treatment of tomato leaf spot disease.
[0054] 1. Experimental setup
[0055] The experiment used uniformly sized, intact Shandong Shouhe tomato seeds. The seeds were first soaked in a 3% sodium hypochlorite solution for 5 minutes, then rinsed several times with distilled water. The seeds were then placed in 50°C warm water for 20 minutes to awaken the seeds. The seeds were then placed in a shaking incubator at 30°C, 150 rpm, and incubated in the dark for 32 hours, with water changes every 8 hours. When the seedlings were 3 mm long, they were planted in pots containing a 3:1 mixture of wood ash and vermiculite under full-spectrum LED grow lights. The cultivation conditions were a 28°C / 23°C day / night temperature and a 13 / 11 hour light cycle. Watering was done once daily, morning and evening, to maintain a stable relative humidity.
[0056] In a potted experiment to investigate the efficacy of ZnO-TiO2@MSC in controlling tomato leaf spot, six treatments were set up: A positive control, PC, was used for tomato plants without pathogen infection and without ZnO-TiO2@MSC; a negative control, NC, was used for tomato plants infected with pathogens and without ZnO-TiO2@MSC; and a treatment group, where each plant was sprayed with 10 ml of ZnO-TiO2@MSC at four concentrations: 500 μg / mL, 1000 μg / mL, 2000 μg / mL, and 4000 μg / mL. Three replicates were set up for each potted treatment.
[0057] 2. Research on the prevention and control effect of tomato leaf spot disease.
[0058] Pseudomonas syringae Pst The effectiveness of DC3000 in controlling bacterial leaf spot on tomatoes directly reflects the antibacterial activity of ZnO-TiO2@MSC on tomatoes. The leaf lesion diameter and incidence rate were recorded over a 15-day observation period. The incidence rate was calculated as follows:
[0059] Incidence rate = (number of diseased leaves / number of surveyed leaves) × 100.
[0060] The experimental results are as follows Figure 6 and Figure 7 As shown, tomato plants treated with ZnO-TiO2@MSCs maintained healthy growth for 15 days after inoculation. In contrast, untreated plants developed characteristic yellow lesions upon infection, which gradually spread across the leaves. The disease-suppressing effect of ZnO-TiO2@MSCs was concentration-dependent, with the highest effect observed at a concentration of 2000 μg / mL, where pathogenicity on leaves decreased to 0.4% after 15 days. Notably, infection increased slightly when the concentration was increased to 4000 μg / mL, indicating that optimal disease control is achieved at moderate concentrations.
[0061] 3. Changes in the number of pathogenic bacteria on leaves.
[0062] Use a 6mm diameter borer to randomly punch six leaf discs onto the treated leaves. Soak the discs in 75% alcohol for 10 seconds to remove surface bacteria. Rinse the discs twice with sterile water and remove excess water with sterile filter paper. Transfer the discs to a centrifuge tube containing 500μL of 10mM MgCl₂ and grind for 20 seconds to obtain a grinding solution. Then, add 100μL of the grinding solution to 900μL of sterile water. Pathogen counts were performed to observe changes in the plant pathogen population before and after treatment. The control rate formula is shown below.
[0063] Prevention and treatment rate = [(disease index of control group - disease index of prevention and treatment group) / disease index of control group] × 100.
[0064] The disease index standard in the formula is: level 0, no disease; level 1, 1 to 3 pieces; level 2, 3 to 5 pieces; level 3, 5 to 8 pieces; level 4, 8 to 11 pieces.
[0065] The experimental results are as follows Figure 8 As shown, the control efficacy of tomato leaf spot disease was significantly enhanced to 75.35% under 2000 μg / mL ZnO-TiO2@MSC treatment. Furthermore, by recording infected leaves, calculations showed that the total number of pathogenic bacteria in tomatoes decreased significantly when treated with 2000 μg / mL, while the total number of colonies increased at 4000 μg / mL compared to 2000 μg / mL. Furthermore, the control efficacy against leaf spot disease in the four treatment groups of 500 μg / mL, 1000 μg / mL, 2000 μg / mL, and 4000 μg / mL was 26.67%, 42.56%, 79.83%, and 58.55%, respectively. This indicates that ZnO-TiO2@MSC only produces significant control effects at appropriate concentrations; concentrations that are too high or too low have little effect on bacterial leaf spot disease.
[0066] 4. Study on the biological effects of ZnO-TiO2@MSC on tomatoes.
[0067] (1) Determination of tomato plant growth.
[0068] After the tomato plants were sprayed with ZnO-TiO2@MSC and grew for 15 days, 10 pots were randomly selected, and the leaf length, plant height, and root length were measured and recorded. The roots of different treatments were scanned using a root scanner.
[0069] The experimental results are as follows Figure 9 and Figure 10As shown in the results, in addition to disease inhibition, ZnO-TiO2@MSC treatment also promoted the overall growth and development of the plants, with plant height, leaf length and root length significantly increased 15 days after treatment.
[0070] (2) Determination of photosynthetic function.
[0071] After the tomato plants were sprayed with ZnO-TiO2@MSC and grown for 15 days, the net photosynthetic rate, transpiration rate, water use efficiency and stomatal conductance of the tomato leaves under different treatment conditions were measured at 13:00 using a photosynthetic meter.
[0072] The experimental results are as follows Figure 11 As shown, ZnO-TiO2@MSC treatment also enhanced various photosynthetic parameters. At 2000 μg / mL of ZnO-TiO2@MSC, net photosynthetic rate, transpiration rate, stomatal conductance, and water use efficiency increased by 81.3%, 83.9%, 80.5%, and 71.4%, respectively. These improvements suggest that ZnO-TiO2@MSC can protect stomatal openings, enhance cellular water absorption, and promote chloroplast function in tomato leaves.
[0073] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
Claims
1. A method for preparing a nanocomposite material ZnO-TiO2@MSC, characterized in that: The steps include: S1. Soaking corn straw in a hydrochloric acid solution to remove heavy metals, washing it, treating it with an ammonium hydroxide solution to expose its pore structure, and then drying and crushing it to obtain modified straw powder; S2, adding the acid solution catalyst to the titanium source premix to initiate sol formation; The modified straw powder is added to the sol, stirred to produce a gel, and the gel is dried and then calcined in a gradient manner to obtain TiO2@MSC, thereby preparing a TiO2@MSC suspension; S3, mixing the TiO2@MSC suspension and the ZnO nanoparticle suspension to obtain a mixed suspension, stirring the mixed suspension to generate a precipitate doped with TiO2@MSC and ZnO nanoparticles, removing the solvent, washing, drying, and calcining the precipitate at a constant temperature to obtain a nanocomposite material ZnO-TiO2@MSC; The volume ratio of anhydrous ethanol, tetrabutyl titanate and acetylacetone in the titanium source premix is 20:10:1; The volume ratio of the acid solution catalyst, which is 60% to 70% by mass of nitric acid solution, water and anhydrous ethanol, is 1.1:9:32; The mass volume ratio of the modified straw powder, titanium source premix, and acid solution catalyst is 0.5 g:93 mL:42.1 mL; The mass ratio of TiO2@MSC and ZnO nanoparticles in the mixed suspension is 1:
1.
2. The method for preparing the nanocomposite material ZnO-TiO2@MSC according to claim 1, characterized in that: In S1, the gradient calcination program is as follows: starting from the air ambient temperature, heating at a rate of 10°C / min to 500°C for 90 min, then heating to 550°C for 90 min, and finally heating to 600°C for 90 min; In S2, the constant temperature calcination condition is 500°C for 180 min.
3. The nanocomposite material ZnO-TiO2@MSC prepared by the method according to claim 1 or 2.
4. The use of the nanocomposite material ZnO-TiO2@MSC according to claim 3 in the preparation of antibacterial products, characterized in that: The antibacterial product is a pesticide or a bacteriostatic agent.
5. The use according to claim 4, characterized in that The pesticide is a pesticide for preventing and treating tomato leaf spot.
6. The use according to claim 5, characterized in that The pathogen of tomato leaf spot is Pseudomonas syringae ( Pseudomonas syringae ).
7. The use according to claim 5, characterized in that The concentration of the nanocomposite material ZnO-TiO2@MSC in the pesticide is 2000 μg / mL.
8. Use of the nanocomposite material ZnO-TiO2@MSC according to claim 3 in the preparation of a tomato growth promoting product.
9. The use according to claim 8, characterized in that The tomato growth promotion includes promoting the growth of tomato plant height, leaf length and root length, and also includes improving the net photosynthetic rate, transpiration rate, stomatal conductance and water use efficiency of tomatoes.